Strengthening emotional intelligence intervention on behavior changes of mothers in stunting prevention - Sari, Rita Kartika; Mayangsari, Citra Primavita; Mashoedi, Imam Djamaluddin; Intan, Yulice Soraya Nur; Trisnadi, Setyo; Aprilyanti, Dwi Fikha (Intelektual Pustaka Media Utama, 2024)
This study aimed to determine the effect of applying Emotional intelligence reinforcement to changes in stunting prevention behavior at the Kedung 2 Health Center, Jepara. This study employed a cross-sectional approach and data from participants at the Kedung 2 Public Health Center in Jepara. Public Health Center, Jepara. Participants were taken by purposive sampling according to predetermined maternal criteria, and 82 participants were obtained. Quasi-experimental research methods with two groups of emotional intelligence strengthening design, pre-intervention and post-intervention. Data collection used a questionnaire to measure the emotional intelligence of respondents and stunting prevention behavior. The data were then analyzed using the SPSS program. The correlation value shows that there is a strong relationship between the strengthening of emotional intelligence interventions and changes in maternal stunting prevention behavior, with a correlation value of 0.905 and a significance value of less than 0.001. The results of the T-test also showed significant behavioral changes in stunting prevention behavior before and after the application of strengthening emotional intelligence, with a significance value of 0.008. Strengthening emotional intelligence has a strong positive correlation with stunting prevention behavior, and the results of the T-test show that there is a significant effect on the results of stunting prevention behavior between before and after strengthening emotional intelligence. As a result, strengthening maternal emotional intelligence should be a priority to prevent stunting.